SORGUM DEVELOPMENT PROSPECTS IN NORTH SUMATRA SUPPORTING FOOD DIVERSIFICATION - Nelva Meyriani; Rafida Khairani (Sean Institute, 2023)
The food issue, which is still a hot topic of discussion, still needs attention. The increase in food imports shows the weakness of food in a region. The importance of solutions to overcome this problem is food crops which can become a new hope for food security and food self-sufficiency so that agriculture can become self-sufficient in food. Sorghum is a food crop that can be used as a solution to develop on dry land. Judging from the climate conditions of North Sumatra and soil conditions, this plant is suitable for cultivation in North Sumatra. This plant diversification can be made into several processed noodles, bread, cakes and so on so that it can simultaneously boost the economy of North Sumatra.